The Scandal of the Evangelical Mind - Noll, Mark A. (Grand Rapids Eerdmans, 1994)
"The scandal of the evangelical mind," says historian Mark Noll, "is that there is not much of an evangelical mind." This critical yet constructive book explains the decline of evangelical thought in North America and seeks to find, within evangelicalis
Keywords: Evangelicalism -- United States. Learning and scholarship -- Religious aspects -- Christianity. Evangelicalism